EDEN ISS: A Plant Cultivation Technology for Spaceflight - Zabel, Paul; Zeidler, Conrad (Springer Verlag, 2019)
Despite the fact that high-closure bio-regenerative life support systems (BLSS) are not required for short-duration missions, it is well accepted that such systems are a required element for sustained human presence in space. Plants flown on various space-based platforms from Salyut to ISS have until now been used to further our understanding of the effects of the spaceflight environment on plant growth and to enhance the technology required for the maintenance of a sufficiently controlled on-orbit growth environment. While small-scale payloads have been sufficient to address these two aims, it is now becoming technically feasible to incorporate larger-scale on-orbit facilities that can provide fresh food on-board. The all-in-one approach of implementing higher plants in BLSS (air, water, waste recycling, as well as food production and improved crewmember well-being) has a huge advantage for future human space exploration missions. But this approach first needs to be tested on Earth and ISS in order to prove its reliability and applicability. The EDEN ISS partners built a space greenhouse test facility and operation started in February 2018 near the Neumayer Station III research station in Antarctica.